New type of charge and magnetic order in the ferromagnetic Kondo lattice - Garcia, Daniel Julio (2000)
We study numerically the one dimensional ferromagnetic Kondo lattice, a model widely used to describe nickel and manganese perovskites. By including a nearest neighbor Coulomb interaction (V) and a superexchange interaction between the localized moments (K), we obtain the phase diagram in parameter space for several dopings at T=0. Due to the competition between double and superexchange, we find a region where the formation of magnetic polarons induces a charge ordered (CO) state which survives also for V=0. This mechanism should be taken into account in theories of charge ordering involving spin degrees of freedom.